PENGARUH MASSAGE EFFLEURAGE TERHADAP PENURUNAN INTENSITAS SKALA NYERI DISMENORE PADA REMAJA PUTRI DI MAN 2 PADANG - yuanita ananda (Jurnal Keperawatan Abdurrab, 2018)
Dysmenorrhea is menstrual pain cause interference activity for a few hours or a few days. The prevalence of dysmenorrhea in Indonesia reached 64.25% and in West Sumatra reached 57.3%. MAN 2 Padang obtained in 80% had dysmenorrhea and causes 46% of young women is difficult to move, 27% do not learn and 7% concentration was unconscious for not being able to overcome the pain. One non-pharmacologic therapy to reduce dysmenorrhea namely effleurage massage. The objective of the study was to find out the the effect of effleurage massage to decrease intensity pain scale of dysmenorrhea in adolescent girls of MAN 2 Padang in 2017. This type of the study was Pre-Experimental Design with One Group Pretest-Posttest Design. The study was conducted in MAN 2 Padang. The study population was adolescent girls who have dysmenorrhea of 26 people. Total sample of 19 people with technique accidental sampling. The data were analyzed by univariate and bivariate analysis using paired sample t-test. The results of the study showed that the average intensity pain scale of dysmenorrhea before effleurage massage of 4.89 and after the massage effleurage 2.95. From the result of the statistical test, it was found out that the p value was 0.000 (p<0,05), which meant that there was an effect of effleurage massage to decrease intensity pain scale of dysmenorrhea in adolescent girls in MAN 2 Padang. There was an effect of effleurage massage to decrease intensity pain scale of dysmenorrhea in adolescent girls. It is suggested that adolescent girls to apply effleurage massage to reduce pain of dysmenorrhea, both in school and outside of school.